2003
DOI: 10.1128/cdli.10.2.308-314.2003
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Matrix Metalloproteinase 9 and Tissue Inhibitor of Metalloproteinase 1 during the Acute Phase of Kawasaki Disease

Abstract: Kawasaki disease (KD) is an acute, self-limiting, multisystem vasculitis of unknown etiology affecting infants and young children. Unless treated promptly with high-dose intravenous gamma globulin and aspirin, patients frequently develop coronary aneurysms. Previously, matrix metalloproteinase 9 (MMP-9), which is secreted complexed to tissue inhibitor of metalloproteinase 1 (TIMP-1), has been implicated in abdominal aortic aneurysm formation. Since the clinical and pathological features of KD include inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…But despite the fact that MMP-9 levels were elevated in affected hearts in our murine model of KD, there was no correlation between circulating MMP-9 levels and enzymatic activity in affected coronary arteries (25). This is in accordance with data from cases of fatal KD, which show MMP-9 expression specifically localized to the site of coronary artery lesions (26), and the conflicting reports regarding circulating MMP-9 levels in affected children (22)(23)(24)(25). Degradation of elastin is one of the hallmarks of aneurysm formation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…But despite the fact that MMP-9 levels were elevated in affected hearts in our murine model of KD, there was no correlation between circulating MMP-9 levels and enzymatic activity in affected coronary arteries (25). This is in accordance with data from cases of fatal KD, which show MMP-9 expression specifically localized to the site of coronary artery lesions (26), and the conflicting reports regarding circulating MMP-9 levels in affected children (22)(23)(24)(25). Degradation of elastin is one of the hallmarks of aneurysm formation.…”
Section: Discussionsupporting
confidence: 76%
“…MMP-9 may have a role in coronary artery aneurysm formation in KD. Despite conflicting data on serum levels of MMP-9 during the acute phase of KD (22)(23)(24)(25), local MMP-9 expression at the site of coronary artery aneurysms in children with KD has been documented (26). Circulating levels of molecules known to act locally may not be useful biomarkers of disease; this is especially relevant to enzymatic activity, which is tightly regulated at multiple levels including the local tissue environment (25).…”
mentioning
confidence: 99%
“…3). It was reported that there was no correlation between blood TIMP and MMP production levels and disease severity in multiple patients with Kawasaki disease, and an imbalance of these levels contributed to the development of vasculitis (24,25). It was also suggested that the imbalance of TIMP and MMP is a factor contributing to the development of vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…The proteolytic enzyme activity of pro-MMP-9 was measured by gelatin zymography (18). Briefly, protein concentrations were determined with the Bio-Rad DC (Bio-Rad Laboratories; Hercules, CA) protein assay kit from conditioned media and cell-lysate of PC-3 cells cultured under growing conditions as described previously (18).…”
Section: Methodsmentioning
confidence: 99%
“…The proteolytic enzyme activity of pro-MMP-9 was measured by gelatin zymography (18). Briefly, protein concentrations were determined with the Bio-Rad DC (Bio-Rad Laboratories; Hercules, CA) protein assay kit from conditioned media and cell-lysate of PC-3 cells cultured under growing conditions as described previously (18). Total protein (15 μg) was mixed with non-denaturing buffer (125 mM Tris-HCl, 4% SDS, 20% glycerol, 0.004% bromophenol blue) and the protein samples were subjected to electrophoresis through a 10% Zymogram Ready Gel (Bio-Rad Laboratories).…”
Section: Methodsmentioning
confidence: 99%